Some improvements of the Katznelson-Tzafriri theorem on Hilbert space - Seifert, D (American Mathematical Society, 2015)
This paper extends two recent improvements in the Hilbert space setting of the well-known Katznelson-Tzafriri theorem by establishing both a version of the result valid for bounded representations of a large class of abelian semigroups and a quantified version for contractive representations. The paper concludes with an outline of an improved version of the KatznelsonTzafriri theorem for individual orbits, whose validity extends even to certain unbounded representations.